Validity of the modified landing error scoring system (LESS–M) for screening non-contact ACL injury risk using a lateral single-leg jump-landing task. - Subedi, Miraj; Sinsurin, Komsak; Suttiwong, Jatuporn; Warathanagasame, Pinyada; Gao, Yu (Physical Therapy in Sport, 2025)
To develop the Landing Error Scoring System–Modified (LESS–M) and assess its content and concurrent validity. Content and concurrent validity study. Online expert survey and laboratory-based testing. Five field experts and 29 healthy individuals. Content Validity Index (CVI) and Spearman's rank correlation between LESS–M scores and standard 3D motion analysis. All experts endorsed the lateral single-leg jump-landing task and the modified assessment tool. The ave-CVI and I-CVI were 0.97 and 0.8–1.0, respectively. Moderate correlations were found between the LESS–M score and both knee valgus (ρ = 0.425; p = 0.001) and hip adduction moment (ρ = 0.446; p = 0.001) at peak vertical ground reaction force (vGRF). The LESS–M demonstrated strong content validity based on expert consensus and showed moderate concurrent validity with 3D motion capture for assessing lateral single-leg jump landing. It may be a potential tool for identifying individuals at risk for non-contact ACL injury. Nonetheless, further investigation is required to determine an appropriate cutoff score and to assess the reliability of the LESS–M for broader application. • The original LESS limitation was jump-landing test with doubled legs in forward direction. • The LESS-M is designed to assess lateral single-leg jump-landing tasks. • The LESS-M demonstrated strong content validity and moderate concurrent validity. • The LESS-M shows moderate concurrent validity with the 3D motion analysis. • The LESS-M could serve as a potential tool for identifying non-contact ACL injury risk.